Whole genome analysis reveals the distribution and diversity of plasmid reservoirs of NDM and MCR in commercial chicken farms in China - Xuan Wu; ZhiRong Zhang; Rong Xiang (Microbiology Spectrum)
ABSTRACT The increase in multidrug-resistant (MDR) Enterobacteriaceae presents a significant challenge to clinical treatment, particularly in infections where carbapenems and colistin serve as the last-resort antimicrobial agents. In this study, we isolated 119 non-repetitive gram-negative bacteria from MacConkey medium supplemented with imipenem and colistin. The isolates were dominated by Klebsiella pneumoniae (58.0%, n = 69) and Escherichia coli (31.1%, n = 37). The predominant sequence types (STs) of E. coli were ST226, ST1286, and ST11738, whereas K. pneumoniae displayed ST152, ST395, and ST709 as major types. Genomic analysis identified mcr-1/3/8/9 in 44 strains and blaNDM in 63 strains across various species. IncX3 (n = 57) and IncFII (n = 5) were the most common blaNDM-5-carrying plasmid types. Several plasmid replicons were associated with mcr genes, including IncI2, IncX4, and novel plasmids. Remarkably, we discovered four combinations of blaNDM and mcr co-occurrence in 28 isolates, including blaNDM-5/mcr-1, blaNDM-5/mcr-3, blaNDM-5/mcr-8, and blaNDM-5/mcr-9. Our findings reveal that chicken farms are significant reservoirs for both blaNDM and mcr genes, with frequent co-occurrence of these resistance determinants. The presence of these genes alongside other resistance factors, such as blaESBL, highlights a critical public health risk. This study underscores the need for enhanced surveillance and intervention strategies to mitigate the spread of MDR pathogens from agricultural environments to clinical settings.IMPORTANCEThis study reveals that commercial poultry farms in China serve as critical reservoirs for MDR gram-negative bacteria harboring carbapenemase (blaNDM) and mobilized colistin resistance (mcr) genes. By analyzing 119 isolates, we uncovered extensive genetic diversity and plasmid-mediated co-occurrence of these resistance determinants, enabling bacteria to evade nearly all available treatments. Alarmingly, the horizontal transfer of resistance genes via highly mobile plasmids facilitates their spread across microbial communities and potentially into clinical settings. These findings underscore the urgent need to address antibiotic overuse in agriculture and strengthen surveillance under the One Health framework. The persistence of MDR pathogens in poultry environments highlights a significant risk for zoonotic transmission, emphasizing the necessity of coordinated interventions to curb the global antimicrobial resistance crisis.